Studi Fenomenologi Komunikasi Penyandang Tuna Netra Pada Yayasan Mahatmiya Tabanan Bali - Wicaksana, Gede Satya; Mardiksa Putra , I Putu Gede Buda; Indiana, Ni Made (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2026)
This study aims to analyze the phenomenology of interpersonal communication and the formation of self-concept among visually impaired individuals at Yayasan Mahatmiya Tabanan, Bali. This research employs a qualitative method with a phenomenological approach to explore participants lived experiences. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that interpersonal communication plays a central role in shaping meaningful relationships, enhancing self-confidence, and strengthening the self-concept of visually impaired individuals. Empathy, responsiveness, and openness are key elements that support effective communication. In addition, environmental support, including social acceptance and inclusive communication practices, significantly contributes to the development of positive self-perception. This study highlights the importance of inclusive communication environments in rehabilitation institutions and contributes to the development of communication studies, particularly in the context of disability and social interaction.